Risk of renal stone events in primary hyperparathyroidism before and after parathyroid surgery: controlled retrospective follow up study. Issue 7368 (12th October 2002) - Mollerup, Charlotte L; Vestergaard, Peter; Frøkjær, Vibe Gedsø; Mosekilde, Leif; Christiansen, Peer; Blichert-Toft, Mogens
Abstract: Aim : To study the risk of renal stone episodes and risk factors for renal stones in primary hyperparathyroidism before and after surgery. Design : Register based, controlled retrospective follow up study. Setting : Tertiary hospitals in Denmark. Participants : 674 consecutive patients with surgically verified primary hyperparathyroidism. Each patient was compared with three age- and sex-matched controls randomly drawn from the background population. Hospital admissions for renal stone disease were compared between patients and controls. Risk factors for renal stones among patients were assessed. Main outcome measures : Number of renal stone episodes; comparison of hospital admissions for renal stones in patients and controls; assessment of risk factors for renal stones. Results : Relative risk of a stone episode was 40 (95% confidence interval 31 to 53) before surgery and 16 (12 to 23) after surgery. Risk was increased 10 years before surgery, and became normal more than 10 years after surgery. Stone-free survival 20 years after surgery was 90.4% in patients and 98.7% in controls (risk difference 8.3%, 4.8% to 11.7%). Patients with preoperative stones had 27 times the risk of postoperative stone incidents than controls. Before surgery, males had more stone episodes than females and younger patients had more stone episodes than older patients. Neither parathyroid pathology, weight of removed tissue, plasma calcium levels, nor skeletal pathology (fractures) influenced the risk of renal stones. After surgery, younger age, preoperative stones and ureteral strictures were significant risk factors for stones. Conclusions : The risk of renal stones is increased in primary hyperparathyroidism and decreases after surgery. The risk profile is normal 10 years after surgery. Preoperative stone events increase the risk of postoperative stones. Stone formers and non-stone formers had the same risk of skeletal complications.